Demonstration of a hybrid collisional soft-x-ray laser - Nickles, P. V., author; Sandner, W., author; Shlyaptsev, V. N., author; Kalachnikov, M. P., author; Bortolotto, F., author; Rocca, Jorge J., author; Janulewicz, K. A., author; American Physical Society, publisher (Colorado State University. Libraries, 2001)
We report on a demonstration of x-ray-ultraviolet amplification following collisional excitation in a discharge-created plasma waveguide irradiated by a picosecond optical laser pulse. A capillary discharge was used to generate a sulfur plasma column with a large concentration of Ne-like ions and a radially concave electron density profile. The intense short laser pulse rapidly heated the electrons, producing amplification in the 3p 1S0-3s 1P1 transition of Ne-like S at 60.8 nm. The integrated gain-length product obtained exciting a 3-cm-long capillary with a 0.46-J short laser pulse is 6.8. The beam divergence was observed to decrease as a function of plasma column length, reaching 2.5 mrad for 30-mm-long capillaries. This hybrid laser pumping scheme could lead to a new generation of efficient tabletop soft-x-ray lasers.